Policy Solutions to Close Gender Gaps in the Agriculture Sector in Nigeria - World Bank (Washington, DC, 2022)
Substantial gender gaps exist in labor force participation and productivity in the agriculture sector in Nigeria. Closing the gender productivity gap in agriculture could lead to sizable gains in the Nigerian economy, boosting gross domestic product. Key factors driving the gender gaps in agriculture include women farmers’ limited use of farm inputs, choice of lowvalue crops, and lower productivity of hired labor. To successfully close gender gaps, policy makers not only need a detailed account of what drives these gaps, but also a rigorous evidence base on cost-effective policy options. This brief offers guidance on interventions that could be adopted to address the underlying constraints faced by women farmers in Nigeria. These recommendations could also meaningfully inform the framework and implementation of the National Gender Policy on Agriculture.